Sepsis 2016 Agra, India. Issue 1 (February 2016) - Sharma, Surinder; Rohatgi, Anurag; Bajaj, Mansi; Sprung, Charles; Morales, Ricardo; Kasdan, Harvey; Reiter, Allon; Volker, Tobias; Meissonnier, Julien; Beloborodova, Natalia; Moroz, Viktor; Bedova, Aleksandra; et al.
Table of contents P1 D-Dimer in adult patients with presumed sepsis and their clinical outcomes Surinder Kumar Sharma, Anurag Rohatgi, Mansi Bajaj P2 Diagnosis of infection utilizing Acellix CD64 Charles L. Sprung, Ricardo Calderon Morales, Harvey Kasdan, Allon Reiter, Tobias Volker, Julien Meissonnier P3 High levels of phenylcarboxylic acids reflect the severity in ICU patients and affect phagocytic activity of neutrophils Natalia Beloborodova, Viktor Moroz, Aleksandra Bedova, Yulia Sarshor, Artem Osipov, Katerina Chernevskaya P4 The role of bacterial phenolic metabolites in mitochondrial dysfunction Nadezhda Fedotcheva, Ekaterina Chernevskaya, Natalia Beloborodova P5 The early diagnosis of severe sepsis and judgment of rapid transport to critical care center: better prognostic factor Hisashi Imahase, Kosuke C Yamada, Yuichiro Sakamoto, Miho Ohta, Ryota Sakurai, Mayuko Yahata, Mitsuru Umeka, Toru Miike, Hiroyuki Koami, Futoshi Nagashima, Takashi Iwamura, Satoshi Inoue P6 Translational neuromodulation of the immune system Zhifeng Li, Dennis Grech, Patrick Morcillo, Alex Bekker, Luis Ulloa P7 Pathway-level meta-analysis reveals transcriptional signature of septic shock Samanwoy Mukhopadhyay, Abhay D Pandey, Samsiddhi Bhattacharjee, Saroj K Mohapatra P8 Antibiotic dosing in septic patients on the critical care unit - a literature review Julie K Wilson P9 Pandemic ofEscherichia coli clone O25: H4-ST131 producing CTX-M-15 extended spectrum- β- lactamase- as serious cause of multidrug resistance extraintestinal pathogenicE. coli infections in India Savita Jadhav, Rabindra Nath Misra, Nageswari Gandham, Kalpana Angadi, Chanda Vywahare, Neetu Gupta, Deepali Desai P10 Detection and characterization of meningitis using a DDA-based mass spectrometry approach Anahita Bakochi, Tirthankar Mohanty, Adam Linder, Johan Malmström P11 Diagnostic usefulness of lipid profile and procalcitonin in sepsis and trauma patients Dimple Anand, Seema Bhargava, Lalit Mohan Srivastava, Sumit Ray P12 Heparin – a novel therapeutic in sepsis? Jane Fisher, Peter Bentzer, Adam Linder P13 Hypothalamic impairment is associated with vasopressin deficiency during sepsis Luis Henrique Angenendt da Costa, Nilton Nascimentos dos Santos Júnior Carlos Henrique Rocha Catalão, Maria José Alves da Rocha P14 Presepsin (soluble CD14 subtype) is a dependable prognostic marker in critical septic patients Alfredo Focà, Cinzia Peronace, Giovanni Matera, Aida Giancotti, Giorgio Settimo Barreca, Angela Quirino, Maria Teresa Loria, Pio Settembre, Maria Carla Liberto, Bruno Amantea P15 Safety and efficacy of gelatin-containing solutions versus crystalloids and albumin - a systematic review with quantitative and qualitative summaries Christiane Hartog, Christiane Hartog, Claudia Moeller, Carolin Fleischmann, Daniel Thomas-Rueddel, Vlasislav Vlasakov, Bram Rochwerg, Philip Theurer, Konrad Reinhart P16 Immunomodulatory properties of peripheral blood mesenchymal stem cells following endotoxin stimulation in an equine model Anna E. Smith, Sandra D. Taylor P17 Frequency and outcome of early sepsis-associated coagulopathy Christopher Da Costa, Amanda Radford, Terry Lee, Joel Singer, John Boyd, David Fineberg, Mark Williams, James A Russell